Effect of a Diet Supplemented with Nettle (Urtica dioica L.) or Fenugreek (Trigonella Foenum-Graecum L.) on the Content of Selected Heavy Metals in Liver and Rabbit Meat - Sylwia Ewa Pałka; Ewa Drąg-Kozak; Łukasz Migdał; Michał Kmiecik (Animals, 2022)
The literature on herbal additives for rabbit feed offers little information on the use of nettle and fenugreek. Both of these herbs are valuable sources of vitamins and minerals. These herbs affect the growth, health, and meat quality of rabbits. They regulate the digestive system, stimulate the appetite, have a positive effect on the functioning of the immune system, and exhibit antibacterial activity. The purpose of the present study was to determine the effect of nettle (Urtica dioica L.) leaves or fenugreek (Trigonella foenum-graecum L.) seeds in the feed on the content of selected heavy metals in the liver and meat of the rabbit. The rabbits were divided into three groups: group C (n = 20; 10♂ and 10♀) was fed ad libitum with a complete feed, N group (n = 20; 10♂ and 10♀) was fed a complete mixture with 1% added nettle, and group F (n = 20; 10♂ and 10♀) was fed with a complete mixture with 1% added fenugreek. The experiment lasted 7 weeks (from the 35th to the 84th day of the rabbits’ lives). All the rabbits were slaughtered on the 84th day of age, with a body weight of about 2.6 kg. The concentration of heavy metals (Zn, Cu, Ni, Mn, Fe, Pb, Cd) was determined by the atomic absorption spectrometry (AAS). The additives to the feed significantly affected the content of elements in both the liver and the meat of rabbits (p < 0.05). The highest level of the heavy metals, regardless of the used diet, was recorded in the liver (p < 0.05). The meat (m. longissimus lumborum) and the liver of rabbits fed with herbal fodder contained less tested metals than in animals fed with fodder without additives (p < 0.05). Moreover, more essential metals were found in the liver of rabbits fed with fenugreek than rabbits fed with nettle. In the meat and liver of rabbits, the permissible content of cadmium and lead was not exceeded. Additionally, male livers had a significantly higher content of copper and manganese compared to female livers (p < 0.05). It is important to study the content of heavy metals in the used animal herbal feed additives and their interaction with each other, as they affect the distribution of elements in tissues and organs.